Evaluation of the Effectiveness of Sewage Treatment Plant Performance in GKM Green Tower Building - Maha Rendra, Aldera Aji (Universitas Mercu Buana, 2025)
Wastewater or wastewater is the remaining water that is disposed of, originating from households, industries, offices, and other public places. A sewage treatment plant (STP) is a process of reusing wastewater and removing contaminants from wastewater. This study evaluates the Sewage Treatment Plant system in the GKM Green Tower Building. This study aims to analyze the performance of the Sewage Treatment Plant (STP) in the GKM Green Tower building and to determine the effectiveness of the performance of the Sewage Treatment Plant (STP) in the GKM Green Tower building. The parameters used in this study were pH (acidity), COD, BOD, TSS, oil and grease, Total Coliform, and Ammonia, which complies with Domestic Wastewater Quality Standards Based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.68/ Menlhk-Setjen/2016. Recycled water in the GKM Green Tower building is used to flush closed urinals and water plants. It was found that the results of clean wastewater management in the GKM Green Tower building still look cloudy and smelly. Based on the results of domestic wastewater monitoring tests at GKM Green Tower in August / prior to analysis, several parameters exceeded the quality standards, namely TSS and Total Coliform. The maintenance carried out so far on the Sewage Treatment Plant (STP) system in the GKM Green Tower Building is still not good, which is the cause of the ineffectiveness of the wastewater that has been managed so far. The results of the second test conducted in November showed a decrease in the numbers between the TSS 4 and Total Coliform parameters between 1100. So that they were in accordance with the quality standards set by the government Ministry of Environment.